Proyecto de implementación de una planta procesadora de jugos y compotas de frutas - Arévalo Anilema, María Laura (2009)
The project to install a pilot plant in the Province of Santa Elena who produces and commercializes compotes and juices of fruits, is basically an option To improve the Infantile Nutrition of the poor children of the principal cantons of the Ecuadoran Coast. Thanks to the production of the Province of Holy Elena, it has thought that it will be possible have a normal supply of the fruits all the year round, with the seasonal periods established for each of the fruits that are going to be tried, beside a sufficient production existed to supply to the market. To achieve an ideal positioning of the compotes and juices as products richly in proteins is very important to bearing in mind is that the distribution systems of these products are developed in an efficient way, to the effect that the compotes and the juices are available in all the places where the persons of scanty resources could acquire them. It has been chosen for the installation of a process plant of flesh of fruit in the city of Guayaquil, because it makes the flexibility possible as for the final product; this one can serve for several type of fruits, which does not border to the project and believe perspectives in the future to try other profitable products. The project is viable from the financial point of view for the investor. The obtained indicators, they reflect that the project is in aptitude to return the investmen